Transnational partnerships in higher education in China: The diversity and complexity of elite strategic alliances (UCL Press, 2016)
Transnational partnerships between universities can illustrate the changing political, social, and cultural terrain of global higher education. Drawing on secondary data analysis of government educational statistics, university web pages, and a comprehensive literature review, this article focuses on transnational partnerships with particular reference to China in order to illuminate the diversifying relationships between networks of global universities. International partnerships develop in historical, geographic, social, and cultural contexts and the analysis of Chinese universities' partnerships across different social, cultural, and geopolitical contexts indicates that, even within the elite groups of universities, transnational partnerships are diverse and complex. This article aims to demonstrate that the spread of internationalization in the form of transnational partnership is not uniform but is influenced by complex contextual factors, some of which are accentuating inequalities in the system.